Islamic Economics and Wealth Distribution: Alternative Strategies for Addressing Global Issues - Afifah, Dhiya Dwi; Yunilhamri, Muhammad Syauqi; Mahyarni (JAWI : Journal of Ahkam Wa Iqtishad, 2025)
Wealth distribution in Islamic economics is an important pillar in creating sustainable social justice and welfare. This study aims to describe the concept of distribution in the perspective of Islamic economics, identify the sharia principles that underlie it, and explain the mechanisms of wealth distribution through instruments such as zakat, infaq, sadaqah, and waqf. The research method employed is qualitative descriptive using literature review techniques, with primary data sourced from the Quran and Hadith, and secondary data from academic literature and previous studies. The findings reveal that the Islamic distribution system balances individual property rights with social responsibility, prevents the accumulation of wealth among certain groups, and ensures equitable access to economic resources. Islamic distribution instruments have proven relevant in addressing global economic inequality, both through classical application during the time of the Prophet Muhammad SAW and the Khulafaur Rasyidin, as well as contemporary adaptation in the digital age. With a combination of spiritual and moral values and practical mechanisms, wealth distribution in Islam offers a fair, sustainable, and inclusive alternative strategy in facing global issues.